Botulinum toxin for the management of depression: An updated review of the evidence and meta-analysis. (March 2021) - Schulze, Jara; Neumann, Insa; Magid, Michelle; Finzi, Eric; Sinke, Christopher; Wollmer, M. Axel; Krüger, Tillmann H.C.
Abstract: Botulinum toxin (BTX) treatment of glabellar frown lines is one of the most common procedures in aesthetic medicine. In addition to its cosmetic effect, the neurotoxin has been shown to have a positive influence on mood and affect. Several randomized clinical trials (RCTs) have examined the effect of botulinum toxin on the treatment of depression. Combining the results of the five RCTs in a random effects meta-analysis revealed that patients treated with BTX showed a more intense improvement of depressive symptoms in comparison to subjects that received placebo injections ( d  = 0.98). Despite methodological limitations, the results of this study emphasize the effectiveness of BTX in the treatment of depression and therefore pave the way for its use in the field of psychiatry.